2023
DOI: 10.1111/psyg.13014
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in the association between physical frailty and life satisfaction among older adults in India

Abstract: BackgroundOne of the sustainable development goals' (SDGs) primary goals (Goal 3) is to ensure healthy lives and promote well‐being for persons of all ages. While extensive literature documents the link between physical frailty and low life satisfaction (LLS) among older adults, research of this nature is limited within low and middle‐income countries including India. The purpose of this study was to examine the association between physical frailty and life satisfaction among community‐dwelling older men and w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 74 publications
0
2
0
Order By: Relevance
“…The growing elderly population poses a great challenge to social development, and the increasing base of the elderly population and strained healthcare resources are affecting the quality of life of the elderly (21). Research on life satisfaction among older adults is increasing, and influences such as age (22), gender (23), psychological condition (24), economic status (25), health-related behaviors (26), and child care (27) are often included as key influences in studies, depending on the topic of study. Relevant studies have also demonstrated the relevance of the above influences on the self-assessment of life satisfaction in older adults.…”
Section: Influencing Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…The growing elderly population poses a great challenge to social development, and the increasing base of the elderly population and strained healthcare resources are affecting the quality of life of the elderly (21). Research on life satisfaction among older adults is increasing, and influences such as age (22), gender (23), psychological condition (24), economic status (25), health-related behaviors (26), and child care (27) are often included as key influences in studies, depending on the topic of study. Relevant studies have also demonstrated the relevance of the above influences on the self-assessment of life satisfaction in older adults.…”
Section: Influencing Factorsmentioning
confidence: 99%
“…Notably, gender differences were observed, with older women exhibiting higher levels of selfassessment of life satisfaction than older men. Discrepancies exist in current research on gender-based differences in the selfassessment of life satisfaction among older adults (22). However, supporting studies posit that women's proficiency in expressing negative emotions may contribute to higher self-assessment levels in older women than men (41,42).…”
Section: Personal Status and Its Negative Correlation With Elderly Li...mentioning
confidence: 99%